Atmospheric pressure chemical vapor deposition (APCVD) grown bi‐layer graphene transistor characteristics at high temperature. Issue 7 (15th May 2014) - Qaisi, Ramy M.; Smith, Casey E.; Hussain, Muhammad M.
Abstract We report the characteristics of atmospheric chemical vapor deposition grown bilayer graphene transistors fabricated on ultra‐scaled (10 nm) high‐κ dielectric aluminum oxide (Al2O3) at elevated temperatures. We observed that the drive current increased by >400% as temperature increased from room temperature to 250 °C. Low gate leakage was maintained for prolonged exposure at 100 °C but increased significantly at temperatures >200 °C. These results provide important insights for considering chemical vapor deposition graphene on aluminum oxide for high temperature applications where low power and high frequency operation are required. (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)